DEVELOPMENT COMMUNICATION AND SOCIAL CHANGE IN THE DYNAMICS OF LAND ACQUISITION FOR THE KUNINGAN DAM NATIONAL STRATEGIC PROJECT, WEST JAVA - Fuad Faizi; Alfian Febriyanto; Intan Tsuroya (UIN Siber Syekh Nurjati Cirebon, 2024)
The communication process between the government and the community in the land acquisition for the Kuningan Dam national strategic project resulted in conflict and injustice, which in turn led to the failure of the development of the welfare of affected communities. This research project aims to examine the development communication and social change in communities affected by the Kuningan Dam project in Kuningan Regency, with a particular focus on the concept of Communication for Development and Social Change as proposed by Wilkins and Mody. This research employs a qualitative methodology with a case study approach, utilising data collection techniques such as interviews, observation, and documentation in affected villages in Kuningan Regency. Informants were selected using purposive and snowball sampling, with data verified through triangulation. In the aftermath of the development project, the predominantly agricultural communities were compelled to transition to alternative livelihoods due to the loss of cultivable land. However, many encountered difficulties in adapting, resulting in economic setbacks and a deceleration in their socio-economic adaptation process. This research contributes to emphasising the importance of fair, transparent and inclusive development communication in national strategic projects in Indonesia. It does so by highlighting the role of communication in exacerbating social inequalities, compensation inequalities and government unpreparedness in supporting the socio-economic transition of affected communities. The findings of this research demonstrate that the construction of the Kuningan Dam gave rise to social tensions as a consequence of the following factors: the acquisition of land on an unfair basis; the lack of effective communication between the government and the community; the unequal distribution of compensation; and the socio-economic impacts, which served to exacerbate the difficulties faced by affected communities, particularly in relation to changes in their livelihoods.